Combination of IFITM1 knockdown and radiotherapy inhibits the growth of oral cancer. Issue 10 (21st September 2018) - Yang, Jie; Li, Lei; Xi, Yan; Sun, Ruimei; Wang, Hu; Ren, Yanxin; Zhao, Liufang; Wang, Xiaoli; Li, Xiaojiang
Abstract : This research aimed to analyze the effect of IFITM1 on the radioresistance of oral neoplasm. Using a multi‐group heat map from GSE9716 analysis of the GEO database, IFITM1 was determined to be a relevant radioresistance gene. The TCGA database was analyzed before the expression of IFITM1 was analyzed. IFITM1 expression was quantified by quantitative RT‐PCR and immunohistochemistry in 19 paired oral neoplasm cases. The effects of time and dose of radiation on IFITM1 expression level in CAL27 and TSCC1 cell lines were tested by quantitative RT‐PCR. Oral neoplasm cells were transfected with siRNA after radiotherapy to disturb IFITM1 expression. After this, the survival rates, cell apoptosis, caspase‐3 viability, expression and γ‐H2AX were detected using colony formation, flow cytometry, western blot and immunofluorescence, respectively. Western blot was used for STAT1/2/3/p21‐related protein and phosphorylation changes. Finally, an in vivo nude mice tumor model was established to verify the effect of IFITM1 on oral neoplasm cells radioresistance. Through microarray analysis, the head and neck neoplasm radioresistance‐related gene IFITM1 was found to be overexpressed. IFITM1 overexpression was verified not only using the TCGA database but also in 19 paired cases of oral neoplasm tissues and cells. With increases of dose and time of radiation, the expression of IFITM1 was increased in CAL27 and TSCC1 cell lines. Furthermore, si‐ IFITM1 may restrain cell proliferation, DNA damage and cell apoptosis in oral neoplasm cell lines. Finally, pSTAT1/2/p21 was found to be upregulated while pSTAT3/p‐p21 was downregulated due to IFITM1 inhibition after radiotherapy. The evidence suggested that IFITM1 in combination with radiotherapy can inhibit oral neoplasm cells. Abstract : As a whole, the overexpression of IFITM1 could upgrade the cell proliferation and cell apoptosis in CAL27 and TSCC1 cells. On the contrary, cell proliferation and apoptosis could be inhibited via radiotherapy. Furthermore, the effect will be much better in combination with inhibition of IFITM1. Therefore, this study might support some progresses for the treatment of oral neoplasm.